Determination of 20(S)-protopanaxadiol in human plasma by HPLC–MS/MS: application to a pharmacokinetic study - Feifan Xie; Sanwang Li; Zeneng Cheng; Xingling Liu; Hong Zhang; Peijiong Li; Zhi Liu; Xin Guo; Peng Yu (Acta Pharmaceutica Sinica B, 2013)
A rapid, specific and sensitive HPLC–MS/MS method was developed and validated for the determination of 20(S)-protopanaxadiol (PPD) in human plasma. PPD and the internal standard PD were extracted from plasma by liquid–liquid extraction with cyclohexane–methylene dichloride (2:1, v/v). The separation was performed on a HyPURIYTY C18 column using methanol–5 mM ammonium formate (90:10, v/v) as mobile phase at a flow rate of 0.35 mL/min. Mass spectrometric detection was carried out by electrospray ionization (ESI) in the positive ion mode using multiple reaction monitoring (MRM). The monitored transitions were m/z 425.4→217.2 for PPD and at m/z 461.4→425.5 for PD. The method was linear over the range 0.512–100 ng/mL with a lower limit of quantification (LLOQ) of 0.512 ng/mL. The mean extraction recovery of PPD was greater than 78.2% and no significant matrix effect was detected. The intra- and inter-day precisions were less than 10% and the biases below 4% for PPD. The validated method was applied to a three-level single-dose clinical pharmacokinetics study of 12 healthy Chinese volunteers and the main pharmacokinetic parameters of PPD were obtained.